Kinetics of Enzymatic Hydrolysis of Passion Fruit Peel using Cellulase in Bio-ethanol Production - Megawati Megawati; Astrilia Damayanti; Radenrara Putri; Angga Pratama; Tsani Muftidar (Reaktor, 2020)
This research aims to study the hydrolysis of passion fruit peel using cellulase and its evaluation for ethanol production. Passion fruit peel is a fruit processing waste that has not been utilized properly. Passion fruit peel contains holo-cellulose (64% w/w), which can be converted into ethanol through hydrolysis followed by fermentation. Hydrolysis using cellulase is more efficient and its fermentation using yeast to produce ethanol is common. The hydrolysis is carried out at various enzyme ratios (3, 5, 7, and 9% v/v) and at temperature 30 oC, material concentration 5 g/100 mL, pH 4-5, and shaking speed 160 rpm. The kinetics chosen were heterogeneous models; they were the fractal model by Valjamae and Kopelman. Before being hydrolyzed, the essential oil and pectin in passion fruit peel were extracted, because the compositions were quite high; the results were around 16.23 and 11.36% w/w, respectively. The effect of the enzyme ratio to the sugar concentration by hydrolysis is very significant. At 9 h, the glucose concentration reached 45.38, 51.86, 60.50, 66.00 g/L at various enzyme ratios of 3, 5, 7, 9% v/v. During the hydrolysis, the glucose concentration continues to increase and starts to decrease after 9 h. Hydrolyzate solution fermentation obtained from hydrolysis in various enzyme ratios showed consistent results; the higher the enzyme ratio and glucose, and the higher the ethanol will be (5.6, 6.8, 7.6, and 8.9% v/v). The kinetics model by Valjamae is more appropriate to describe the enzymatic hydrolysis mechanism of passion fruit peel than Kopelman. The fractal exponent values obtained from Valjamae and Kopelman models were 0.28 and 0.27. In Valjamae model, the enzyme ratio rises, from 3 to 9% v/v, the rate constant rises from 0.22 to 0.53 1/h. In Kopelman model, the rate constant rises too, from 0.21 to 0.51 1/h.Keywords: bio-ethanol; cellulase; enzymatic hydrolysis; fractal kinetic; passion fruit peel